Dermatophyte infection of the male genitalia - Das Jayanta; Sengupta Sujata; Gangopadhyay Asok (Wolters Kluwer Medknow Publications, 2009)
Dermatophyte infection is a very common disease, but that of the male genitalia is said to be rare. Here we report four cases of dermatophyte infection of the male genitalia, of which one had lesion on the penis alone, one had lesions on the penis and the groins, one had lesions on penis and scrotum, and the other had involvement of scrotum, penis and groins. Two patients gave history of application of steroid-containing preparations and another had diabetes mellitus. Culture of the scraping of the lesional skin yielded Trichophyton rubrum in two cases and Epidermophyton floccosum in the other two. All cases resolved completely with topical terbinafine with or without oral antifungals.